OCCUPATIONAL CONTACT DERMATITIS IN FARMERS - Melina Tombeng; IGK Darmada; IGN Darmaputra (Universitas Udayana, 2013)
Occupational contact dermatitis is common condition seen in the primary care setting. Farmer has the highest incidence for occupational contact dermatitis. This because of the job is exposed to chemical and wet works. Occupational contact dermatitis is divided to irritant contact dermatitis and allergic contact dermatitis. Whether both have different in pathogenesis, they give similar symptoms. Precise diagnosis is needed to confirm the diagnosis and to exclude the others. Treatment should be aimed at controlling inflammation, restoring the skin’s natural barrier, and avoiding irritants and potential allergens. There are a range of prevention strategies, which include: elimination or substitution of harmful exposures; technical control measures; personal protection; identification of susceptible individuals; and others.